Comments on "Carnivorous Walrus and Some Arctic Zoonoses" - Manning, T.H. (ARCTIC, 1961)
In this interesting paper (Arctic 13:111-22) F. H. Fay suggests that polar bears and walrus contract trichinosis primarily from the flesh of ringed and bearded seals. I do not necessarily dispute this, but I do suggest that Fay unduly discounts other sources of infection. Bears are omnivorous scavengers and at times will eat, or try to eat, the most unlikely substances. Armstrong gives the stomach contents of a bear shot in Prince of Wales Strait as a few raisins, small pieces of pork fat, some tobacco leaves, and two pieces of common adhesive plaster. I have known them to chew into cans of engine oil. They walk long distances overland and along the shore and must frequently find carcasses of foxes, small mammals, and occasionally of other bears. That polar bears do not hesitate to eat the flesh of their own species is well known. Cases are mentioned by Edvard Bay and by Stefansson, and I have had caches of bear meat broken into and partly eaten by other bears. Occasionally cubs may be killed deliberately and eaten. In 1958-9 the Eskimos at Resolute reported that bears were eating trapped foxes, and during the same season five out of 25 fox diaphrams examined were infected with Trichinella. In 1949 on Prince Charles Island we saw places where bears had turned over stones, presumably in search of lemmings. When lemmings are really abundant it would be possible for a bear to obtain considerable numbers with very little effort. In the areas where ground squirrels are common it is not unlikely that these are also sometimes eaten. In the past when Eskimos abandoned their dead or gave them a very perfunctory burial, even humans may have been a source of infection. .